Influence of the cautionary legend on non-nutritive sweetener (NNS) on preference and healthfulness perception. - Claudia Calderon; Tania C Aburto; Carolina Batis; Alejandra Contreras-Manzano; Simón Barquera (PLoS ONE)
In 2020, Mexico's Congress mandated front-of-package warning labels (FOPWL) and two cautionary legends; one of which for non-nutritive sweeteners (NNS) with a statement "Contains NNS. Avoid in children". The aim of the study was to assess the influence of the "excess in sugar" warning label (WL) and NNS cautionary legend on preference and healthfulness perception of fruit-based beverages among parents of 5-10 year-olds. Also, to test if parents' preferences and perceptions differed by nutrition knowledge and previous knowledge on NNS. Data from the EPHA niñ@s (Study of the Perception and Dietary Habits in Children, for its acronym in Spanish) cohort were analyzed (n = 844). Parents were asked to choose between 100% juice and nectar with added sugars above the cut-off point, and between the latter and nectar with NNS marketed as "light", and to rate how healthy they considered each product at two different timepoints. At time 1, products were shown without the FOPWL; at time 2, nectar with excess sugar had the "excess sugar" WL and nectar with NNS had the cautionary legend on NNS. General Linearized Models (GLM) were used to assess changes in preference and perceived healthiness. Interaction terms assessed the impact of nutrition knowledge and NNS awareness. The study found that FOPWL significantly shifted parental preferences towards 100% juice over nectar with "excess sugar" (15.4% increase, p<0.001), and the latter over nectar with NNS (21.8% increase, p<0.001). Similarly, the FOPWL decreased the perceived healthiness of both nectar with "excess sugars" and nectar with NNS. The effect of labels on healthfulness perception was strongest among parents with low to medium nutrition knowledge and no prior knowledge of NNS. The inclusion of FOPWL seems to aid parents in making better-informed decisions regarding the nutritional quality of beverages for their children.